Nutrition knowledge, body image and food security risk amongst development rugby league players - Buchanan, T. D.; Sharples, A.; Gough, L.; Black, A. D.; Black, K. E. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: This study aimed to describe the nutrition knowledge, food security risk and eating disorder risk of development male rugby league players. METHODS: Sixty athletes from one Australian professional rugby league club volunteered. A cross sectional online survey questionnaire consisted of three sections (Eating Disorders Inventory (EDI-3), Nutrition Knowledge and Food Security). All athletes completed the online survey without assistance using a personal electronic device. RESULTS: The mean total knowledge score was 65.7±13.1%. There was a positive relationship between age and knowledge score, P=0.050, r2=0.06. The majority of players had breakfast everyday (N.=45, 73.8%), took pack lunches (N.=33, 55.0%), and had homemade evening meals (N.=55, 91.7%). The majority of players ate more than 1 hour before training (N.=45, 75%) and all players (n=60, 100%) ate within half an hour of training finishing. The majority of participants agreed that nutrition could influence physical and cognitive aspects of nutrition however, skill-based activities were perceived by fewer participants to be influenced by nutrition. The majority (N.=38, 63.3%) had high food security, six (10.0%) had marginal food security, whereas 10 (16.7%) and six (10.0%) had low and very low security respectively. CONCLUSIONS: These results show a concerning levels of eating disorder risk, food insecurity and poor nutrition knowledge amongst male development rugby league players. However, it does show that they believe nutrition can impact their health and performance, and they do mostly appear to adhere to the nutrition principals for optimising health and performance.